2015
DOI: 10.1016/j.ejcb.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of lysosome-associated membrane protein 3 (LAMP3) enhances cellular vulnerability against proteasomal inhibition

Abstract: The family of lysosome-associated membrane proteins (LAMP) includes the ubiquitously expressed LAMP1 and LAMP2, which account for half of the proteins in the lysosomal membrane. Another member of the LAMP family is LAMP3, which is expressed only in certain cell types and differentiation stages. LAMP3 expression is linked with poor prognosis of certain cancers, and the locus where it is encoded was identified as a risk factor for Parkinson's disease (PD). Here, we investigated the role of LAMP3 in the two main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…The resistance induced by LAMP3 is primarily directed towards proteasome inhibitors used during chemotherapy. In conclusion, it has been found that increased expression of LAMP3 contributes to the development of autophagy and cell survival [6] [27]. It is important when developing new therapies, including molecularly targeted therapies, to inhibit the specific cytokine activating the signaling pathway involved in a particular disease.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The resistance induced by LAMP3 is primarily directed towards proteasome inhibitors used during chemotherapy. In conclusion, it has been found that increased expression of LAMP3 contributes to the development of autophagy and cell survival [6] [27]. It is important when developing new therapies, including molecularly targeted therapies, to inhibit the specific cytokine activating the signaling pathway involved in a particular disease.…”
Section: Discussionmentioning
confidence: 90%
“…This finding indicates that inhibition of autophagy may be an effective treatment for advanced stage cancer [21]. Autophagocytosis can be induced, among other things, by UPR-dependent signaling pathway activated by hypoxia or nutrient deficiency [6] [9]. The precise mechanism of action of this pathway is not yet known, and the genes involved in this process have not yet been identified [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations